2006
DOI: 10.1182/blood-2005-03-1259
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of high-risk acute leukemia with a recipient (autologous) vaccine expressing transgenic human CD40L and IL-2 after chemotherapy and allogeneic stem cell transplantation

Abstract: CD40L generates immune responses in leukemia-bearing mice, an effect that is potentiated by IL-2. We studied the feasibility, safety, and immunologic efficacy of an IL-2-and CD40L-expressing recipientderived tumor vaccine consisting of leukemic blasts admixed with skin fibroblasts transduced with adenoviral vectors encoding human IL-2 (hIL-2) and hCD40L. Ten patients (including 7 children) with high-risk acute myeloid (n ‫؍‬ 4) or lymphoblastic (n ‫؍‬ 6) leukemia in cytologic remission (after allogeneic stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 58 publications
(63 reference statements)
0
50
0
Order By: Relevance
“…Our study adds to a growing body of clinical studies that established safety, feasibility, and biological activity of whole tumor cell-based vaccination for patients with hematologic malignancies (17,29,30). A number of features unique to our vaccination approach may have contributed to the observed expansion of leukemia-reactive CD8 + T cell responses.…”
Section: Discussionmentioning
confidence: 86%
“…Our study adds to a growing body of clinical studies that established safety, feasibility, and biological activity of whole tumor cell-based vaccination for patients with hematologic malignancies (17,29,30). A number of features unique to our vaccination approach may have contributed to the observed expansion of leukemia-reactive CD8 + T cell responses.…”
Section: Discussionmentioning
confidence: 86%
“…A previous study showed that CD40L and IL-2 exert a congenerous antitumor effect (23), and Rousseau et al applied these results from the in vitro and animal experiments into a clinical setting in which a mixture of primary cultured skin fibroblasts infected with Ad IL-2 and Ad CD40L, and autologous leukemia cells were administered by intradermal injection. The pertinent leukemia cell responses of the patients were then monitored (24). CD40L and IL-2 are co-expressed in the same carrier, and in future applications it may be possible to reduce the number of steps (by only producing a carrier) and reduce the cost.…”
Section: Discussionmentioning
confidence: 99%
“…The promising vaccine responses achieved recently using leukemia cells combined with CD40 ligand and IL-2 indicate that antigen-presenting cell maturation in the presence of leukemia antigens can lead to the generation of detectable anti-ALL T-cell responses in patients. 31 Our study suggests that the use of CpG ODN may provide a simpler strategy to achieve both the killing of the residual leukemia and coincident maturation of antigen-presenting cells necessary to efficiently prime protective T-cell responses in vivo.…”
Section: Durable Protection From All Induced Bymentioning
confidence: 99%